Design, Characterization and Application of The SCMNPs@PC/VB1-Zn as A Green and Recyclable Biocatalyst for Synthesis of Pyrano[2,3-c]pyrazole and 4H-benzo-[b]-pyran Derivatives - Fang Hou; Wei Zheng; Nasser Yousefi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Eco-friendly and reusable solid acid catalysts (SCMNPs@PC/VB1-Zn) were identified as one of the most effective basic catalysts for the composition of a pot, three-component pyrano[2,3-c]pyrazoles. Methyl-1-phenyl-1H-pyrazole-5(4H)-one, benzaldehyde and malononitrile in high yield at 80 °C. SCMNPs@ PC/VB1-Zn reports the simple and efficient catalysis of a three-component pot reaction of dimedone, aldehydes, and malononitrile to 4H-benzo-[b]-pyran derivatives. This magnetic nanocatalyst can be recycled more than 6 times without dramatically reducing performance with respect to reaction time and efficiency. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).